1983
DOI: 10.1111/j.1651-2227.1983.tb09865.x
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin, Acth and Neonatal Haemodynamics

Abstract: Pohjavuori, M. and Fyhrquist, F. (Department of Paediatric Cardiology, Children's Hospital, University of Helsinki, and The Minerva Institute for Medical Research, Helsinki, Finland). Vasopressin, ACTH and neonatal haemodynamics. Acta Paediatr Scand, Suppl. 305: 79–83, 1983.—In 21 normal deliveries, high concentrations of AVP and ACTH in cord blood were associated with higher blood pressure and lower skin temperature, indicating peripheral vasoconstriction. Following Caesarean section after the onset of labour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…Fetal stress as indicated by meconiumpresent in the amniotic fluid is associated with elevated cord AVP levels [10], but the effect of birth on asphyxia in elevating AVP levels [11] only lasts for the first 2 days [12]. The type of delivery also influences AVP levels [13], vaginal delivery versus caesarean section being associated with higher levels [14]. More of our CLD infants were delivered vaginally and they had lower Apgar scores, but their AVP levels only differed significantly from those of the non-CLD infants from day 3 onwards.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal stress as indicated by meconiumpresent in the amniotic fluid is associated with elevated cord AVP levels [10], but the effect of birth on asphyxia in elevating AVP levels [11] only lasts for the first 2 days [12]. The type of delivery also influences AVP levels [13], vaginal delivery versus caesarean section being associated with higher levels [14]. More of our CLD infants were delivered vaginally and they had lower Apgar scores, but their AVP levels only differed significantly from those of the non-CLD infants from day 3 onwards.…”
Section: Discussionmentioning
confidence: 99%
“…Although newborn's kidneys are still immature and their capability to concentrate urine is limited (3), it has been demonstrated that there is a significant nonlinear positive correlation between AVP concentration and osmolality (U‐Osm) (4). Earlier studies have also shown that the mode of delivery affects AVP levels at birth (2,5–9). The precise role of high AVP concentrations in response to labour and birth remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…These studies were performed in term neonates; in VLBW infants blood pressures were similar in infants delivered vaginally versus those delivered by cesarean section. 61,[100][101][102] Likewise in the study by Zubrow and colleagues, stepwise multiple linear regression analysis did not identify route of delivery as a significant determinant of blood pressure variation in preterm neonates. 60 Breech delivery has been associated with blood pressure in the lower range of normal.…”
Section: Route Of Deliverymentioning
confidence: 88%
“…101 Pohjavuori and Fyhrquist found an association between cord blood arginine vasopressin (AVP) and adrenocorticotropic hormone (ACTH) levels, route of delivery, and blood pressures. 102 Vaginally delivered infants had the highest blood pressures and AVP and ACTH levels, followed by those delivered by cesarean section with labor and then those delivered by elective cesarean section. These studies were performed in term neonates; in VLBW infants blood pressures were similar in infants delivered vaginally versus those delivered by cesarean section.…”
Section: Route Of Deliverymentioning
confidence: 94%